Does a value-added smile curve imply an environmental frown curve? - Wolfgang Schwarzbauer; Virág Bittó; Philipp Koch; Jonathan Steininger (EcoAustria - Institute for Economic Research, 2024)
Global value chains (GVCs) play a crucial role in today's international trade. High value-added activities tend to cluster at the start and the end of GVCs, resulting in a U-shaped relationship across production steps known as the "smile curve". The distribution of CO2 emissions along the value chain, however, is relatively unexplored. Here, we map embodied CO2 emissions in GVCs to test whether emissions are distributed differently across production stages than value-added. We find that activities with high high emissions per unit of labour compensation cluster at early stages (e.g. energy production, mining), while late stages (e.g. retail trade) exhibit lower emission intensities. This results in a downward-sloping emissions curve with tentative evidence of a frown-curve pattern. We explore several examples at different levels of aggregation and provide an interactive platform to explore the mapping of value-added and emissions across GVCs. – – Globale Wertschöpfungsketten (GVCs) spielen heute eine entscheidende Rolle im internationalen Handel. Aktivitäten mit hoher Wertschöpfung tendieren dazu, sich am Anfang und am Ende von Wertschöpfungsketten zu konzentrieren, was zu einem U-förmigen Verlauf entlang der Produktionsschritte führt - der sogenannten "smile curve". Die Verteilung der CO2-Emissionen entlang der Wertschöpfungskette ist jedoch relativ unerforscht. Hier bilden wir die eingebetteten CO2-Emissionen in GVCs ab, um zu testen, ob Emissionen entlang der Produktionsstufen anders verteilt sind als die Wertschöpfung. Wir stellen fest, dass Aktivitäten mit hohen Emissionen pro Einheit Arbeitsentgelt in den frühen Stufen (z.B. Energieproduktion, Bergbau) konzentriert sind, während die späten Stufen (z.B. Einzelhandel) geringere Emissionsintensitäten aufweisen. Dies führt zu einer abwärts gerichteten Emissionskurve mit indikativen Hinweisen auf einen invers U-förmigen Verlauf. Wir untersuchen mehrere Beispiele auf unterschiedlichen Aggregationsebenen und stellen eine interaktive Plattform zur Verfügung, die es ermöglicht die Verteilung von Wertschöpfungs- und Emissionsbeiträgen entlang von verschiedenen GVCs zu erkunden.
Keywords: C67; F18; F62; F63; F64; Q56; 330; Greenhouse gas emissions; Sustainable Development; Transition towards green economy; Global Value Chains; Multi-Regional Input-Output Model; International Trade; Climate change